Euthanasia: comparison between law in Malaysia and the Netherlands / Farah Adlini Hj Mohd Din ... [et al.] - Mohd Din, Farah Adlini; Petrus Langi, Patricia Lawie; Wan Ahmad, Sharifah Hajijah; Abd Ghafar, Sujaihah (2005)
This project paper attempts to identify that euthanasia has been slowly accepted in modern society and also to enhance the level of awareness among Malaysian society regarding euthanasia. Moreover, the objective is also to scrutinize the law of euthanasia in Malaysia and to examine the law of euthanasia in The Netherlands and to inquire into the extent to which physician-assisted death for terminally ill patients is likely to be accepted in Malaysia. The significance of the study is to study the social and moral implication as to euthanasia, the effects to the family and also society as a whole. We also would like to know or identified the religious view and elements in the decision to implement euthanasia in Malaysia and the law established to control and administered euthanasia in socio-medical issue. Data were gathered from medical journals, case law, conducted an interview, and through articles from the internet. The report concludes that there is no possible way for Malaysia to implement euthanasia into its law. The word euthanasia does not exist in The Penal Code.